Utilization of Arbuscular Micorrhizal Fungi to Control Fusarium Wilt of Tomatoes - Theodorsius Pedai; Bambang Hadisutrisno; Achmadi Priyatmojo (Universitas Gadjah Mada, 2015)
Tomato is a vegetable crop which is preferred by the Indonesian people. The problem encountered in tomato production is Fusarium wilt which is known as devastating disease. Studies have been done to solve the problem but effective and inexpensive control technique is still questioned. This study aimed to ascertain the ability of Arbuscular Mycorrhizal (AM) fungi as biological control agent in reducing tomato Fusarium wilt. Research was arranged in a completely randomized design (CRD) consisting of 5 treatments and 10 replications. The treatments were untreated plants, Fusarium oxysporum f.sp. lycopersici inoculated plants, AM fungi inoculated plants, AM fungi + F. oxysporum f.sp. lycopersici inoculated plants, F. oxysporum f.sp. lycopersici + benomyl inoculated plants. The results showed that plants which were inoculated with AM fungi had better growth compared to those which were not inoculated with AM fungi. Moreover, plants which were inoculated with AM fungi showed lower disease intensity compared to untreated plant and inoculated plant with F. oxysporum f.sp. lycopersici + benomyl application. Orthogonal contrast analysis showed plants treated with AM fungi significantly perform better growth and resistance towards infection compared with other treatments. Thus, it concluded that AM fungi had the potency as biological control agent. INTISARITomat merupakan tanaman sayuran yang banyak digemari masyarakat Indonesia. Salah satu pengganggu utama pada tomat adalah penyakit layu Fusarium yang disebabkan oleh Fusarium oxysporum f.sp. lycopersici dan menimbulkan masalah yang serius. Kerugian yang ditimbulkan oleh penyakit tersebut sangat besar sehingga perlu dicari cara pengendalian yang murah, efektif, dan aman. Penelitian yang bertujuan untuk mengetahui kemampuan jamur mikoriza arbuskular (JMA) sebagai agens pengendali hayati dalam menekan penyakit layu Fusarium pada tomat ini dilakukan dengan Rancangan Acak Lengkap (RAL) yang terdiri atas 5 perlakuan dan 10 ulangan. Perlakuan meliputi kontrol, inokulasi F. oxysporum f.sp. lycopersici, inokulasi JMA, inokulasi JMA dan F. oxysporum f.sp. lycopersici, inokulasi F. oxysporum f.sp. lycopersici dan aplikasi fungisida benomil. Hasil penelitian menunjukkan bahwa tomat yang diinokulasi JMA memiliki pertumbuhan yang lebih baik dibandingkan yang tidak diinokulasi JMA. Intensitas penyakit pada tomat yang diinokulasi JMA lebih rendah, baik dibandingkan dengan kontrol maupun dengan perlakuan F. oxysporum f.sp. lycopersici dan aplikasi fungisida. Hasil analisis kontras orthogonal menunjukkan bahwa tomat bermikoriza berbeda nyata bila dibandingkan dengan yang tidak diinokulasi JMA maupun yang diaplikasi benomil. Terjadi peningkatan pertumbuhan tomat dan penekanan intensitas penyakit layu Fusarium, sehingga JMA berpotensi sebagai agens pengendali hayati (APH).